2019
DOI: 10.1029/2019jc015056
|View full text |Cite
|
Sign up to set email alerts
|

Copolarized and Cross‐Polarized SAR Measurements for High‐Resolution Description of Major Hurricane Wind Structures: Application to Irma Category 5 Hurricane

Abstract: C‐band high‐resolution radar (synthetic aperture radar [SAR]) is the only spaceborne instrument able to probe at very high resolution and over all ocean basins the sea surface under extreme weather conditions. When coanalyzed with Stepped Frequency Microwave Radiometer wind estimates, the radar backscatter signals acquired in major hurricanes from Sentinel‐1 and Radarsat‐2 SAR reveal high sensitivity in the cross‐polarized channel for wind speeds up to 75 m/s. The combination of the two copolarized and cross‐p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 60 publications
1
48
0
Order By: Relevance
“…The C-band radar's signal was hardly affected by weak rainfall. However, due to the ambiguity of estimating and separating the contributions of precipitation from winds, eliminating intense rain impact on wind retrieval is still a problem [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The C-band radar's signal was hardly affected by weak rainfall. However, due to the ambiguity of estimating and separating the contributions of precipitation from winds, eliminating intense rain impact on wind retrieval is still a problem [21].…”
Section: Discussionmentioning
confidence: 99%
“…Lat1 and Lon1 are the latitude and longitude of external matching point after shift. In wind retrieval research, the location shift has been proven to be beneficial to collocation and comparison [21]. SAR images were matched with wind references consistent in time and space.…”
Section: Data Collocationmentioning
confidence: 99%
“…Studies have shown that C-band co-and cross-polarized SAR observations can be used to retrieve accurate TC wind fields [24][25][26][27]; the root-mean-square error (RMSE) is about 5 m/s for wind speeds up to 75 m/s compared to the collocated SFMR observations [27]. Moreover, TC centers, radii of maximum wind speed, and the azimuthal wave-number one asymmetry of surface winds have been studied using cross-polarized SAR images [28]. A recent study has shown that SAR-derived highresolution TC wind fields can be used to estimate parameters related to TC wind structure [27].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of remote sensing technology, using radar observation to obtain typhoon wind field information has become an effective method. Synthetic aperture radar (SAR) is unique to probe the sea surface at very high resolution under extreme weather conditions [3]. Compared to the remotely sensed winds derived by microwave scatterometers or radiometers observations, the SAR-derived wind product usually has a much higher spatial resolution to obtain the detailed distribution of hurricane winds, which is useful for capturing the structural characteristics of hurricanes, such as the eye and eyewall.…”
mentioning
confidence: 99%
“…Based on these new findings, several cross-polarized empirical GMFs have been established [9][10][11][12][13][14][15][16]. When coanalyzed with airborne Stepped Frequency Microwave Radiometer (SFMR) wind estimates, the radar backscatter signals acquired in major hurricanes from SAR reveal high sensitivity in the cross-polarized channel for wind speeds up to 75 m/s [3]. This makes the cross-polarization SAR a unique tool in hurricane monitoring.…”
mentioning
confidence: 99%